If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(4 + -1x) = 10 + 2x (4 * 7 + -1x * 7) = 10 + 2x (28 + -7x) = 10 + 2x Solving 28 + -7x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 28 + -7x + -2x = 10 + 2x + -2x Combine like terms: -7x + -2x = -9x 28 + -9x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 28 + -9x = 10 + 0 28 + -9x = 10 Add '-28' to each side of the equation. 28 + -28 + -9x = 10 + -28 Combine like terms: 28 + -28 = 0 0 + -9x = 10 + -28 -9x = 10 + -28 Combine like terms: 10 + -28 = -18 -9x = -18 Divide each side by '-9'. x = 2 Simplifying x = 2
| 5x+15y=135 | | x+x^2+x^3=50 | | 7/9=x/36 | | 44=16-h | | 3/x=9/3 | | 2-6=2y | | 4n^2+16n-84= | | 2-6=27 | | x/40=5/8 | | -3m-8-(2m-5)=-15-5m | | -4y+3(4y+4)=-4-9(4-y) | | 2a-3b=465 | | 3(3x-7)+2(5x+9)=0 | | X/2-x/11=9 | | 2(x-5)+4=5x-3(2+x) | | x+17-4=3+y | | x/6=4=15 | | 8(x-5)+9=8x+2 | | c=17v | | 11x+4y=17 | | 2x+3=2(x+1)1 | | -2x+3x=10 | | -1+15x=15x-1 | | 4x^4y^4+-2xy^2=0 | | 3n-10=21 | | 0=-16t^2+12.51t | | 6000=(40+x)+(40+x)+x+x | | 18b^2+25b-3= | | 10=2(u-5)-6u | | 1474x+4=20 | | 6000=(40+x)(x) | | 0.2(x+60)-0.08(x-30)=8.4 |